Structural and functional insights into S-thiolation of human serum albumins - Nakashima, Fumie; Shibata, Takahiro; Kamiya, Kohei; Yoshitake, Jun; Kikuchi, Ryosuke; Matsushita, Tadashi; Ishii, Isao; Giménez-Bastida, Juan A.; Schneider, Claus; Uchida, Koji (Scientific reports, 2018)
Human serum albumin (HSA) is the most abundant serum protein, contributing to the maintenance of redox balance in the extracellular fluids. One single free cysteine residue at position 34 is believed to be a target of oxidation. However, the molecular details and functions of oxidized HSAs remain obscure. Here we analyzed serum samples from normal subjects and hyperlipidemia patients and observed an enhanced S -thiolation of HSA in the hyperlipidemia patients as compared to the control individuals. Both cysteine and homocysteine were identified as the low molecular weight thiols bound to the HSAs. Intriguingly, S -thiolations were observed not only at Cys34, but also at multiple cysteine residues in the disulfide bonds of HSA. When the serum albumins from genetically modified mice that exhibit high levels of total homocysteine in serum were analyzed, we observed an enhanced S -homocysteinylation at multiple cysteine residues. In addition, the cysteine residues in the disulfide bonds were also thiolated in recombinant HSA that had been treated with the disulfide molecules. These findings and the result that S -homocysteinylation mediated increased surface hydrophobicity and ligand binding activity of HSA offer new insights into structural and functional alternation of serum albumins via S -thiolation.